2007
DOI: 10.1152/ajprenal.00097.2007
|View full text |Cite
|
Sign up to set email alerts
|

Ficoll is not a rigid sphere

Abstract: Polydisperse Ficoll mixtures have been used to explore glomerular sieving. Ficoll appears to be neither absorbed nor secreted by the renal tubule, and so urinary Ficoll concentrations reflect only the glomerular filtration barrier. The literature is contradictory regarding Ficoll's behavior as an idealized spherical solute. Further definition of Ficoll transport will inform interpretation of in vivo results. Flat-sheet membranes comprising a uniform array of slit pores measuring 8 nm by 45 mum were perfused wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
89
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 36 publications
4
89
0
Order By: Relevance
“…In brief, a silicon membrane of extremely uniform slit pores did not retain Ficolls with hydrodynamic radii larger than the pore size of the membrane (19). Further investigations suggested that transport of globular proteins through the membrane was similar to that predicted from first principles by Dechadilok and Deen (11), leading to the conclusion that Ficoll, as had previously been suggested by Rippe, was not a sphere and was possibly not rigid (19).…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…In brief, a silicon membrane of extremely uniform slit pores did not retain Ficolls with hydrodynamic radii larger than the pore size of the membrane (19). Further investigations suggested that transport of globular proteins through the membrane was similar to that predicted from first principles by Dechadilok and Deen (11), leading to the conclusion that Ficoll, as had previously been suggested by Rippe, was not a sphere and was possibly not rigid (19).…”
mentioning
confidence: 74%
“…The solution was then incubated at 80°C for 2 h. After conjugation with AMC, labeled Ficoll was recovered by a PD-10 column. Labeled samples were analyzed by size-exclusion chromatography as previously described, except that the excitation and emission wavelengths of the fluorescence detector were set to the appropriate wavelengths for each fluorophore (17,19).…”
Section: Ficoll Preparation and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the permeability for Ficoll both in the GFB and synthetic membranes apparently lies somewhere between that of globular proteins and dextran (1,3,13,20,28). For example, if the plasma clearance of a bolus dose of albumin was only due to renal excretion, this would imply a plasma half-life of ϳ2,000 h, corresponding to a TER alb of Ͻ0.04% (i.e., Ͼ50 times less than that measured by Vuchkova et al) (29).…”
mentioning
confidence: 91%